Pengembangan e-modul fisika berbasis Contextual Teaching and Learning (CTL) pada materi suhu dan kalor untuk meningkatkan motivasi belajar siswa SMA - Hanifa, Hanifa Nurahmi; Putri, Desy Hanisa; Hamdani, Dedy (Navigation Physics : Journal of Physics Education, 2024)
This study aims to describe the feasibility of e-modules based on contextual teaching and learning (CTL), describe learning motivation after using e-modules, and to describe student responses to CTL-based e-modules on temperature and heat material. This research was conducted in class XI MIPA in one of the Bengkulu City State High Schools in the 2023/2024 academic year. The research method uses the ADDIE model which includes five stages, namely analyze, design, develop, implement and evaluate. This CTL-based e-module has gone through the validation test stage with a score of 90.95% with a very feasible category to be used as a physics learning media in the classroom. The results of the learning motivation questionnaire based on the N-gain value are 0.47 with a moderate category so that it can increase student motivation to learn temperature and heat material. The results of the student response questionnaire received a value of 81.22% in the very good category. This shows that the CTL-based e-module on temperature and heat material gets a good response from students.